2002
DOI: 10.1088/0029-5515/42/3/101
|View full text |Cite
|
Sign up to set email alerts
|

A first analysis of fast ignition of precompressed ICF fuel by laser-accelerated protons

Abstract: The main parameters of the beam required to ignite a precompressed DT fuel, as foreseen by the recently proposed scheme of fast ignition by laser-accelerated protons (Roth et al 2001 Phys. Rev. Lett. 86 436), are studied by 2-D numerical simulations and a simple model. For simplicity, instantaneous proton generation at distance d from the compressed fuel and exponential proton energy spectrum, dn/dε∝exp (-ε/Tp), are assumed. An analytical expression and parametric numerical results are then given for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 18 publications
2
104
0
4
Order By: Relevance
“…Atzeni et al [19] reported for this target a minimum ignition energy of 8.5 kJ. Our calculations show the same ignition energy when the ion scattering is off, while it increases slightly to 8.75 kJ for the FP energy deposition model.…”
Section: A Ion Energy Depositionsupporting
confidence: 71%
See 3 more Smart Citations
“…Atzeni et al [19] reported for this target a minimum ignition energy of 8.5 kJ. Our calculations show the same ignition energy when the ion scattering is off, while it increases slightly to 8.75 kJ for the FP energy deposition model.…”
Section: A Ion Energy Depositionsupporting
confidence: 71%
“…8 that the beams have a penetration into the dense core around 1.5 gcm −2 , and slightly higher for the quasi-monoenergetic ions. These values are higher than the optimal value of 1.2 gcm −2 [19,51] due to the energy deposition in the coronal plasma. The coupling efficiencies, defined as the energy deposited in the DT at densities higher than 200 gcm −3 , for the perfectly collimated beams are 0.58 for the maxwellian proton and carbon beams, and 0.70 for the quasi-monoenergetic carbon ions, similar to those reported in Refs.…”
Section: Energy Depositionmentioning
confidence: 67%
See 2 more Smart Citations
“…Power law fits to the numerical data have given useful scaling laws for the hot spot parameters, for example the hot spot energy requirement E/1kJ= 140(ρ /100gcm -3 ) -1.8 . Modeling specific to proton ignition has also been carried out 11 and adds consideration of transit time spread, and optimum proton energies in the plasma jet.…”
Section: A Ignition Conditionsmentioning
confidence: 99%